Distributed adaptive coordinated tracking for coupled non‐holonomic mobile robots. Issue 18 (1st December 2014) - Qiu, Yilong; Xiang, Linying
Abstract : In this study, a coordinated tracking control problem is studied for coupled non‐holonomic mobile robots with limited information of a reference trajectory. A distributed control law with adaptive time‐varying gains is proposed to guarantee that the robots can form a prespecified geometric pattern while the centroid of the geometric pattern can track the reference signal. By designing the adaptive control gains, the control algorithm of this paper does not require the global knowledge of the upper bound of the leader's control input. Both continuous and discontinuous adaptive protocols are proposed in this study. Finally, simulation examples are presented to verify the theoretical results.